Strategi Perencanaan Jumlah Material Tambahan dalam Memproduksi Semen dengan Pendekatan Taguchi untuk Meminimalkan Biaya Produksi (Study Kasus PT Semen Padang) - Nelvi Irawati; Nilda Tri Putri; Alexie Herryandie Bronto Adi (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2015)
Cement is a construction material with a specific quality that must be meet standard requirements and customer requirements. Through a good and continuous quality control, it will produce cement with consistent quality as its Quality Planning. Cement quality is calculated after adding water by measuring its setting time, compressive strength developing, the heat of hydration, expansion/shrinkage, and its durability to environment effect. In cement application, the primary parameter to determine cement quality is its compressive strength. Some factors that affect compressive strength of cement are reactivity and amount of Tricalcium Silicate (C3S) of Clinker, Clinker free lime (free CaO), amount of SO3 in Cement, the amount of additional materials (insoluble residue/IR and loss on ignition/LOI), and sieve on 45 µm residue of cement. This research is intended to find how insoluble residue/IR, loss on ignition/LOI, and the amount of SO3 will affect compressive strength of cement. Various percentages of IR, LOI, and SO3 in cement will result in different compressive strength. Taguchi Method is applied to determine material proportion. With Orthogonal Array calculation for 3 factors and 4 levels, it will result in 16 calculation running times (L16 4**3). In laboratory scale, cement for this research has been being manufactured and then its compressive strength for 3 days, 7 days, and 28 days will be measured. Determination of optimal proportion will be calculated by statistic method for higher compressive strength and lower manufacturing cost.